Conservative treatment of idiopathic spontaneous pneumoperitoneum in a bedridden patient: a case report - Tanaka, Ryo (Surg Case Rep, 2015)
Idiopathic spontaneous pneumoperitoneum is a rare condition that is characterized by intraperitoneal gas for which no clear etiology has been identified. We report here a case of idiopathic spontaneous pneumoperitoneum, which was successfully managed by conservative treatment. A 77-year-old woman who was bedridden with speech disability as a sequela of brain hemorrhage presented at our hospital with a 1-day history of abdominal distention. On physical examination, she had stable vital signs and slight epigastric tenderness on deep palpation without any other signs of peritonitis. A chest radiograph and computed tomography showed that a large amount of free gas extended into the upper abdominal cavity. Esophagogastroduodenoscopy revealed no perforation of the upper gastrointestinal tract. The patient was diagnosed with idiopathic spontaneous pneumoperitoneum, and conservative treatment was selected. The abdominal distension rapidly disappeared, and the patient resumed oral intake on the 5th hospital day without deterioration of symptoms. Knowledge of this rare disease and accurate diagnosis with findings of clinical imaging might contribute towards refraining from unnecessary laparotomy.